Metabolic responses of thermophilic endospores to sudden heat-induced perturbation in marine sediment samples - Chakraborty, Anirban; Rattray, Jayne E.; Drake, Sienna S.; Matthews, Stuart; Li, Carmen; Jørgensen, Bo Barker; Hubert, Casey R. J. (Frontiers in Microbiology, 2022)
Microbially mediated processes in a given habitat tend to be catalyzed by abundant populations that are ecologically adapted to exploit specific environmental characteristics. Typically, metabolic activities of rare populations are limited, but may be stimulated in response to acute environmental stressors. Community responses to sudden changes in temperature and pressure can include suppression and activation of different populations, but these dynamics remain poorly understood. The permanently cold ocean floor hosts countless low-abundance microbes including endospores of thermophilic bacteria. Incubating sediments at high temperature resuscitates viable spores, causing proliferation of bacterial populations. This presents a tractable system for investigating changes in a microbiome’s community structure in response to dramatic environmental perturbations. Incubating permanently cold Arctic fjord sediments at 50°C for 216 hours with and without volatile fatty acid amendment provoked major changes in community structure. Germination of thermophilic spores from the sediment rare biosphere was tracked using mass spectrometry-based metabolomics, radiotracer-based sulfate reduction rate measurements and high-throughput 16S rRNA gene sequencing. Comparing community similarity at different intervals of the incubations showed distinct temporal shifts in microbial populations, depending on organic substrate amendment. Metabolite patterns indicated that amino acids and other sediment-derived organics were decomposed by fermentative Clostridia within the first 12-48 hours. This fueled early and late phases of exponential increases in sulfate reduction, highlighting cross-feeding of volatile fatty acids as electron donors for different sulfate-reducing Desulfotomaculia populations. Succession of germinated endospores triggered by sudden exposure to high temperature and controlled by nutrient availability offers a model for understanding the ecological response of dormant microbial communities following major environmental perturbations.